2017
DOI: 10.1016/j.bjid.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset neonatal sepsis and the implementation of group B streptococcus prophylaxis in a Brazilian maternity hospital: a descriptive study

Abstract: Although the reduction of EOS incidence was not significant, GBS colonization among pregnant women was high, no cases of neonatal GBS have occurred after implementation of prevention guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
5
1
5
Order By: Relevance
“…The prevalence of ENS found in this study is similar to the numbers found in a recent North-American study, in which the rate of ENS ranged from 1 to 4/1,000 live births, depending on the region of the USA and the time of assessment. 12 Regarding the prevalence of proven ENS, the observed value of 0.3/1,000 live births was lower than the one found in an extensive epidemiological study from the United Kingdom (0.71/1,000 live births) 13 , as well as the findings in the Brazilian study by Freitas et al (1.7/1,000 live births) 14 . This difference can be explained by the inclusion of infants born at term or later PTNB in this study, whereas the other analyses described the global prevalence of ENS, without distinction between gestational ages, once the prevalence is inversely proportional to this factor.…”
Section: Discussioncontrasting
confidence: 61%
“…The prevalence of ENS found in this study is similar to the numbers found in a recent North-American study, in which the rate of ENS ranged from 1 to 4/1,000 live births, depending on the region of the USA and the time of assessment. 12 Regarding the prevalence of proven ENS, the observed value of 0.3/1,000 live births was lower than the one found in an extensive epidemiological study from the United Kingdom (0.71/1,000 live births) 13 , as well as the findings in the Brazilian study by Freitas et al (1.7/1,000 live births) 14 . This difference can be explained by the inclusion of infants born at term or later PTNB in this study, whereas the other analyses described the global prevalence of ENS, without distinction between gestational ages, once the prevalence is inversely proportional to this factor.…”
Section: Discussioncontrasting
confidence: 61%
“…La Figura 1 muestra la incidencia global reportada en distintas latitudes comparada con la reportada en nuestro estudio [24][25][26][27][28][29][30][31][32][33][34][35] . La Figura 2 muestra la variación de la incidencia anual en nuestro centro en comparación con E.U.A.…”
Section: Experiencia Clínicaunclassified
“…La edad mediana materna fue de 20 años (rango [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. La mayoría de las mujeres embarazadas eran primigestas y presentaron cinco o más controles prenatales.…”
Section: Factores Maternos Y Estado De Colonizaciónunclassified
See 1 more Smart Citation
“…En los Estados Unidos predominan las cepas de SBG y los microorganismos gramnegativos 13 . Allí, la incidencia de SN temprana está alrededor de 0.3-0.98 por 1000 nacidos vivos 14,15 , con una mortalidad cerca del 24.4% 16 . Actualmente, existe tendencia al aislamiento de Staphylococcus spp.…”
Section: Introductionunclassified